Benchmarking Transport Infrastructure Construction Costs - United Nations Economic Commission for Europe (United Nations, 2024)
The publication provides a comprehensive overview of the achievements of the UNECE Group of Experts on Benchmarking Transport Infrastructure Construction Costs (GE.4/ WP.5) for the period May 2016 - May 2022. As per its mandate the Group has focused its efforts on: identifying and listing terminologies used in the ECE region for construction costs of inland transport infrastructure and creating a glossary of agreed terminologies and related explanations; identifying and describing models, methodologies, tools, and good practices for evaluating, calculating, and analyzing inland transport infrastructure construction costs; collecting and analyzing data to prepare a benchmarking analysis of transport infrastructure construction costs across the ECE region for each inland transport mode: road, rail, inland waterways – including intermodal terminals, freight/logistics centres and inland ports.